Mechanical Impedance of the Non-loaded Lower Leg with Relaxed Muscles in the Transverse Plane - Ficanha, Evandro Maicon; Ribeiro, Guilherme Aramizo; Rastgaar, Mohammad (Frontiers in Bioengineering and Biotechnology, 2015)
This paper describes the protocols and results of the experiments for the estimation of the mechanical impedance of the humans’ lower leg in the External-Internal (EI) direction in the transverse plane under non-load bearing condition and with relaxed muscles. The objectives of the estimation of the lower leg’s mechanical impedance are to facilitate the design of passive and active prostheses with mechanical characteristics similar to the humans’ lower leg, and to define a reference that can be compared to the values from the patients suffering from spasticity. The experiments were performed with 10 unimpaired male subjects using a lower extremity rehabilitation robot (Anklebot, Interactive Motion Technologies, Inc.) capable of applying torque perturbations to the foot. The subjects were in a seated position, and the Anklebot recorded the applied torques and the resulting angular movement of the lower leg. In this configuration, the recorded dynamics are due mainly to the rotations of the ankle’s talocrural and the subtalar joints, and any contribution of the tibiofibular joints and knee joint. The dynamic mechanical impedance of the lower leg was estimated in the frequency domain with an average coherence of 0.92 within the frequency range of 0 to 30Hz, showing a linear correlation between the displacement and the torques within this frequency range under the conditions of the experiment. The mean magnitude of the quasi-static stiffness of the lower leg (the impedance magnitude averaged in the range of 0-1 Hz) was determined as 4.9±0.74 Nm/rad. The direct estimation of the quasi-static stiffness of the lower leg results in the mean value of 5.8±0.81 Nm/rad. An analysis of variance (ANOVA) shows that the estimated values for the quasi-static stiffness from the two experiments are not statistically different.